Exploring Zimbabwe’s enduring economic challenges and interventionist strategies : showcasing the Zimbabwe agenda for sustainable socio-economic transformation (ZimAsset) - Makaye, Peter; Mapuva, Jephias (Africanus: Journal of Development Studies, 2017)
<span style="color: #000000; font-family: 'Arial Narrow', Arial, Helvetica, Tahoma, Geneva, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Following its victory in the 2013 elections held on 31 July, the ruling ZANU-PF party went about crafting a new economic blueprint, the Zimbabwe Agenda for Sustainable Socio- Economic Transformation (ZimAsset). The blueprint intended to bring about accelerated economic growth and wealth creation in Zimbabwe between October 2013 and December 2018. ZimAsset has four strategic clusters, namely Social Services and Poverty Reduction, Food Security and Nutrition, Infrastructure and Public Utilities `as well as Value Addition and Beneficiation. These clusters are regarded as the basis on which the objectives of the blueprint are anchored as well as the drivers of the development policy. This article provides a critical analysis of this blueprint by taking a historical look at the economic policy of the country and hastens to argue that this country has never been short of blueprints. What has been lacking is the implementation; owing to lack of resources, political will and corruption, among other factors. The economic policy is also bereft of an investment strategy, making it difficult to leverage on the country’s mineral resources. The Indigenization and Economic Empowerment Act of 2008 is not doing the country’s efforts to attract Foreign Direct Investment (FDI) any good because it is in actual fact, driving away potential investors. This article argues that given that ZimAsset’s implementation is premised on the availability of financial resources, which the country does not have, and that FDI is not trickling in, the blueprint is bound to fail. This economic blueprint is ambitious, as it aims to achieve almost everything within a five-year period; and yet the country is thin on resources. Therefore, the blueprint will most likely, not be able to take Zimbabweans out of their economic quagmire.